Strategy for Optimizing Zakat Digitalization in Alleviation Poverty in the Era of Industrial Revolution 4.0 - Santoso, Ivan Rahmat (IKONOMIKA, 2019)
ABSTRACTThe era of innovation is disrupted providing space in the development of digital zakat management systems that are expected to increase public trust and make it easier for muzaki to pay zakat. The management of digital zakat is expected to increase the efficiency and efficiency of services in the management of zakat and increase zakat benefits to realize public welfare and poverty reduction. The research method used is descriptive qualitative with SWOT analysis techniques to analyze corporate strategy factors (strengths, weaknesses, opportunities and threats). This study found a strategy to optimize zakat through the improvement of governance systems and information on zakat-based digitalization institutions. In addition, the information system for mustahik and muzaki database needs to be improved in order to optimize the collection and distribution of zakat.Keywords: Zakat, Optimization, Digital